SWAN ocean wave energy study of the Zambales coastline - Plamenco, Dean Ashton D.
The Zambales coastline is known for its wind resource and for its surfing hotspots along the coast facing the West Philippine Sea. It is also identified as a potential resource area for marine energy systems. Strategically located west of the Philippines, it is less exposed to tropical cyclones and main active faults compared to the regions in the east facing the Pacific. These advantages, the availability of energy resources and lower infrastructure risks may be turned as opportunities for development such as the addition of power systems, which contribute to the thrust towards national energy security. This work has three main objectives. First is to quantify the available energy resource using the Simulating Waves Nearshore (SWAN) model. Data for model wing inputs were taken from the PAGASA Data Center and GEBCO 30-are-second gridded bathymetry data were requested from the Buoy Oceanographic Data Center. The second objective is to model the production of wave energy conversion (WEC) devices in the study area. Monthly wave scatter diagrams were generated and used with the available WEC power matrices (Silva, 2012) to determine monthly power generation at the WEC sites. Performance factors were also studied to provide comparison of these technologies. Lastly, is the application of engineering economic analysis to determine the most suitable, economically viable and cost-competitive WEC technology for an ocean wave farm in the region. The SWAN wave model was able to estimate the wave conditions in the region with a root mean square error of 8.087%. Significant wave heights do not exceed 2 meters and dominant wave directions were observed to be influenced by the combination of monsoons and trade winds. The peak power production is reported in August at the Subic Bay - Silanguin Coast site. The energy resource is classified as low-band resource. Production modeling showed that the most suitable technology is the Pelamis WEC with average AF = 1.00 and CF = 9.25. A 50-MW Pelamis wave farm model yielded a levelized cost of electricity of Php 17.29/kWh.